Health care switching behaviour of the patients in Nepal: an ordered logit model analysis - Adhikari, Shiva Raj (Economic Journal of Development Issues, 2015)
Analysis of health care utilization is becoming ever more difficult as consumer preferences change rapidly and the health care market becomes more complex. A number of studies primarily focused on demand for health care with first consultation of health care providers; however, the consumers have made several visits to the providers without referral from the first provider. The paper utilizes the ordered logit model in compensated demand function with example of Kala Azar (KA) care to understand the demand for health care in switching behaviour of the consumer. The individuals have adopted switching behaviour to minimize the cost of health care; however, due to the treatment failure; the total cost of care has increased with number of visits. Information and service obtaining costs have robustly determined the switching behaviour. The total cost of health care increases with the increase in events of switching behaviour that reduces the economic welfare of the household. The demand analysis of health care, which captures the multiple care seeking events, is appropriate for producing better information for policy maker. DOI: http://dx.doi.org/10.3126/ejdi.v15i1-2.11871 Economic Journal of Development Issues Vol. 15 & 16 No. 1-2, p. 128-147